2021
DOI: 10.3389/fped.2021.702719
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Left Ventricular Hypertrophy in Chronic Kidney Disease—A Pediatric Perspective

Abstract: Cardiovascular diseases (CVD) are a hallmark in pediatric patients with chronic kidney disease (CKD) contributing to an enhanced risk of all-cause and CV morbidity and mortality in these patients. The bone-derived phosphaturic hormone fibroblast growth factor (FGF) 23 progressively rises with declining kidney function to maintain phosphate homeostasis, with up to 1,000-fold increase in patients with kidney failure requiring dialysis. FGF23 is associated with the development of left ventricular hypertrophy (LVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Similarly, renal insufficiency can ultimately lead to uremic cardiomyopathy or myocardial fibrosis [ 40 ]. The fibroblast growth factor (FGF-23) released by CKD is reported to cause myocardial hypertrophy [ 41 ]. All this evidence and many other findings in the literature indicate that kidney disease can accelerate heart disease even before it ravages the kidneys [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, renal insufficiency can ultimately lead to uremic cardiomyopathy or myocardial fibrosis [ 40 ]. The fibroblast growth factor (FGF-23) released by CKD is reported to cause myocardial hypertrophy [ 41 ]. All this evidence and many other findings in the literature indicate that kidney disease can accelerate heart disease even before it ravages the kidneys [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 upregulates hepatic CYP2E1 expression potentially through FGF23-PLCγ/Calcineurin-nuclear factor of activated T cells (NFAT) signaling pathway. Previous studies have demonstrated that FGF23 regulates target gene expression by activating the PLCγ/Calcineurin pathway in hepatocytes and cardiac myocytes [ [52] , [53] , [54] , [55] ]. In this study, we employed a calcineurin inhibitor, cyclosporine A (CysA), to illustrate the involvement of the PLCγ/Calcineurin pathway in FGF23-mediated upregulation of hepatic CYP2E1 expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease is characterized by low αKlotho and 1,25(OH) 2 D levels and elevated circulating FGF23. High FGF23 levels are associated with left ventricular hypertrophy and heart failure [ 138 ]. Furthermore, increased circulating FGF23 additionally exacerbates 1,25(OH) 2 D deficiency, possibly contributing to faster progression of CKD and increased mortality in these patients.…”
Section: Vitamin D and The Renin-angiotensin-aldosterone System (Raas)mentioning
confidence: 99%